Ouabain-Induced Cell Death and Survival. Role of α1-Na,K-ATPase-Mediated Signaling and [Na+]i/[K+]i-Dependent Gene Expression - Lopina, Olga Dmitrievna; Tverskoi, Artem Mikhaylovich; Klimanova, Elizaveta Andreevna; Sidorenko, Svetlana Vadimovna; Orlov, Sergei Nikolaevich (Frontiers in Physiology, 2020)
Cardiotonic steroids (CTS) are plant-derived compounds that are known for many years as therapeutic and cytotoxic agents. They are specific inhibitors of Na,K-ATPase, the enzyme, which pumps Na+ and K+ across plasma membrane of animal cells. Treatment of cells by CTS affects various cellular functions connected with the maintenance of the transmembrane gradient of Na+ and K+. Numerous studies demonstrated that binding of CTS to Na,K-ATPase not only suppresses its activity but also induces some signal pathways. This review is focused on different mechanisms of two CTS effects: their ability 1) to protect rodent cells from apoptosis through the expression of [Na+]i-sensitive genes, and 2) to trigger death of non-rodents cells (so called «oncosis») possessing combined markers of «classic» necrosis and «classic» apoptosis. Detailed study of oncosis demonstrated that the elevation of the [Na+]i/[K+]i ratio is not a sufficient for its triggering. Non-rodent cell death is determined by the characteristic property of “sensitive” to ouabain α1-subunit of Na,K-ATPase. In this case ouabain binding leads to enzyme conformational changes triggering the activation of p38 MAPK signaling. The survival of rodent cells with ouabain-«resistant» α1-subunit is connected with another conformational transition induced by ouabain binding that results in the activation of ERK ½ signaling pathway.